Analisis Pertumbuhan Penjualan Dan Perputaran Modal Kerja Terhadap Profitabilitas PT. Tiga Pilar Sejahtera Food, Tbk Tahun 2012-2016 - Supanji Setyawan; S. Susilowaty (Department of Accounting-Faculty of Economic and Business (FEB), 2018)
This study aims to analyze whether there is influence of variable sales growth and working capital turnover on corporate profitability. Sample in this study is the PT. Tiga Pilar Sejahtera Food, Tbk. Data used in this research is secondary data that of annual report of PT. Tiga Pilar Sejahtera Food, tbk in 2012-2015. Data collection method used is documentation. The result of research with multiple linear regression analysis method showed that the partial sales growth variable had a significant positive effect on profitability while the working capital turnover had no significant effect on profitability. The author recommends that companies pay more attention to, utilize and process resources owned to improve corporate profits, so that the increase in corporate profitability can be achieved.